Management of bovine breeds in Amazonian ecosystems. Pastaza province case study - Vargas Burgos, Julio Cesar (2013)
To contribute to environmental recovery and sustainable local development of livestock in the Pastaza province of the Republic of Ecuador, a factorial model, which controlled for the effects of climate and flat terrain relief in completely randomized design was used to determine the factors that determine the comfort provided by ecosystems to different cattle breeds used in livestock systems. Dynamics of environmental variables that determine the stress conditions for the races that are exploited in the Pastaza province was controlled. To diagnose the methodology described by Benitez et al (2007) as amended by Ramirez et al (2010) were applied for this tool to establish livestock farms used a Geographic Information System for managing livestock systems formulated, which was formed with layers of soil, its limiting factors, precipitation, relative humidity, temperature, evaporation, light hours and ITH complex layers and ordering of races. Characteristics of livestock farms by size of herd was determined, the structure of the herds, the evolution perspective livestock indicators that determine efficiency, slope soil layers, comfort and order of the race. Under the conditions of the Pastaza province is recommended to use in the tropics evolved breeds or crosses of these breeds with specialized genotypes for different purposes, the Bos taurus. It concludes that it is necessary to conduct research leading to the production of information, allowing the creation of a management system for livestock in the province, sort livestock according to the capacity of ecosystems and evaluate different promising genotypes for sustainable livestock production in the Ecuadorian Amazon.